Analysis of Ecotourism Development Typology in Indonesia: A Scoping Review - Nugroho, Albertus Erico Jerry Krisna; Hidayat, Agung; Verdilla, Anastasia (Sriwijaya Journal of Environment, 2025)
This research examines the typology of ecotourism development in Indonesia through a scoping review approach by analyzing 37 scientific articles. The results show seven main categories of ecotourism development: education-based, regional or local potential, community, local wisdom, national regulation or strategy, conservation, and disaster mitigation. Each category illustrates a specific approach tailored to Indonesia's geographical, social and cultural conditions. Community-based approaches and local wisdom support active community engagement, while conservation and disaster mitigation-based approaches emphasize the importance of environmental preservation in the face of climate change. By combining perspectives from various disciplines, this research offers novelty in systematic mapping of ecotourism management. Analysis of the effectiveness of government policies, more in-depth exploration in less accessible areas, and the use of digital technology in tourism area management are some recommendations for further research. These results can be an important reference for readers around the world who are interested in ecotourism practices in tropical and developing countries. In addition, they can provide guidance to support sustainability for policy makers, academics, and ecotourism practitioners.